Espaçamento e população de plantas na cultura da mamona na safra e safrinha: estudo econômico - Petinari, Ricardo Alessandro; Soratto, Rogério Peres [UNESP]; Souza-Schlick, Genivaldo David de; Zanotto, Maurício Dutra [UNESP]; Bergamasco, Sônia Maria Pessoa Pereira (My University, 2011)
Changing weather and light throughout year can influence the grain yield of castor bean, thereby affecting the economic return of the crops. This study aimed to examine the production cost and the profitability of castor bean cultivar FCA-PB, in the 2007/08 and 2008/09 summer harvests and in the 2008 and 2009 off-season harvests, when subjected to different sizes of row spacing and densities of plant population. These results show that the 2007/08 season achieved the best economic results and that the off-season crop is not economically feasible.

Variações das condições climáticas e luminosidade, durante o ano, podem influenciar a produtividade da cultura da mamona e, com isso, prejudicar o retorno econômico da atividade. Assim, este trabalho teve por objetivo analisar o custo de produção e a lucratividade da cultivar de mamona FCA-PB, nas safras de 2007/08 e 2008/09 e nas safrinhas 2008 e 2009, quando submetida a diferentes espaçamentos e populações de plantas. Pelos resultados obtidos, foi possível verificar que a safra 2007/08 apresentou os melhores resultados econômicos e que foi inviável, economicamente, a produção no período de safrinha.
Row spacing and plant population in summer and off-season castor bean crops: an economic study
Keywords: Ricinus communis; Production cost; Profitability indicators; Ricinus communis; Custo de produção; Indicadores de lucratividade